Bioethanol Production from Hydrolysate of Sago Starch Processing Effluent via Simultaneous Saccharification and Fermentation - Micky, Vincent; Estefanny Sonia, Ngalih; Nurashikin, Suhaili; Dayang Salwani, Awang Adeni; Kenny, Daun; Devagi, Kanakaraju; Melissa, Montalbo-Lomboy (The Italian Association of Chemical Engineering, 2025)
The extraction of sago starch generates substantial volumes of starch-rich wastewater, making the hydrolysate a potential substrate for bioethanol production. In this study, simultaneous saccharification and fermentation (SSF), using amylase and Saccharomyces cerevisiae, was conducted on sago effluent hydrolysate (SEH) to produce bioethanol. A commercial starch broth was used as the control to evaluate the efficacy of SEH as an alternative substrate. Both SEH and control exhibited comparable carbohydrate consumption profiles, with 91.70 % of total carbohydrates utilized from SEH, compared to 96.80 % in commercial starch. Ethanol production from SEH peaked at 8.39 g/l (78.02 % Theoretical Ethanol Yield, TEY) within 12 h, in comparison to 8.88 g/l, or 82.57 % TEY, for the commercial starch. However, statistical analyses confirmed that there was no significant difference between the ethanol yields of SEH and the commercial starch broth at the end of the fermentation period. These findings suggest that SEH is a viable and sustainable alternative feedstock for bioethanol production.